Kartagener’s syndrome: A case report - Taušan Đorđe; Ristić Anđelka; Zvezdin Biljana (Vojnosanitetski Pregled)
Introduction. Kartagener’s syndrome is a recessive autosomal disease which is mainly seen to affect ciliary movement. The symptoms of the syndrome are the consequence of the defective motility of the cilia found in the respiratory tract and that results with recurrent lung infections caused by mucus stasis in the bronchi. Case report. A 37-year-old married, male father of one child, presented with a history of productive cough, wheezing, dispnea, headache, temporary fever. In his 9th year of age, 1986, situs inversus, sinusitis and pectus excavatum were diagnosed. In 1994 he was operated for correction of pectus excavatum. Bronchial asthma was diagnosed in 2008 when he was 31. In the last 2 years he had episodes of breathlessness, wheezing, cough, expectoration, headache, fever and fast declining lung function. The patient was treated with combination of inhaled bronchodilatators (inhaled corticosteroids + long-acting β-2 agonist), and occasional administration of antibiotics, oral prednisolone, mucolytics in episodes of exacerbations of disease over a period of 7−14 days. Conclusion. Treatment for patients with this syndrome has not been established yet, but it is important to control chronic lung infections and prevent declining of lung function.